The influence of active involvement on learning outcomes of physics pre-service teachers: A case study of blended learning on statistics course - Andista Candra Yusro; Mislan Sasono; Gilang Primayoga (Universitas PGRI Kanjuruhan Malang, 2020)
This research aimed at identifying the influence of active involvement on blended learning for Statistics course on the learning outcomes of Physics pre-service teacher. This research also attempted to depict the benefits and challenges during the implementation of blended learning in the higher education context, particularly the implementation of blended learning for Statistics course among Physics pre-service teachers. The sample of this research was the entire students of Physics education department who attended Statistics course in the Fifth semester. Based on the results of the research, the active involvement of Physics pre-service teachers during blended learning session on Statistics course contributes as much as 56.5%. While the correlation equation obtained was Y= 44.509 + 0.503 X. The average responses of blended learning given by the Physics pre-service teacher on Statistics course was 81.5%. The implementation of blended learning for Statistics course improves the active involvement of Physics pre-service teachers.